Passenger Service Evaluation In Aceh Province Ulee Flight Port - Bambang Setiawan; Siti Nurlaili Triwahyuni; Wanda Mutiara Anom (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
The Ulee Lheue Ferry Port in Banda Aceh City serves a commercial route between Ulee Lheue - Balohan. The existence of this route is very important in an effort to support economic development in the Sabang region and development in the tourism sector. For this reason, it is necessary to provide services in accordance with statutory regulations in order to carry out good port activities. However, in fact there are still several indicators of service to passengers that are not in accordance with the provisions. Based on these conditions, the authors conducted a literature study on the problems found at the port. Then, an analysis is carried out using a method in order to obtain the results of the analysis as well as proposals for problem solving. The method used to analyze the existing problems is the analysis of the calculation of the level of conformity of passenger service standards in the Minister of Transportation Regulation Number PM 39 of 2015 with existing conditions. Based on the results of the analysis, it was concluded that the appropriate aspect percentage was 44% while the remaining 56% were not. The following aspects are not appropriate, among others: (a) safety aspects such as fire extinguishers that are not maintained, there are no signs for evacuation routes and evacuation gathering points, there is no list of emergency telephone numbers; (b) security aspects such as no information on security disturbances , CCTV at the port is not functioning optimally, the lighting is less intense, (c) comfort aspects such as toilet capacity are sufficient for the comfort of the toilet in a dirty and smelly condition, no temperature control facilities available, no passenger lane (gangway) directly to ships; (d) aspects of convenience / affordability such as no information service on ship trips, porters who are not in uniform; (e) aspects of equality such as no facilities for disabled passengers, facilities for nursing mothers that still do not meet the requirements of Passenger Service Standards.